On sofic systems II - Krieger, Wolfgang (Israel journal of mathematics, 1987)
The results of "On sofic systems I" on topological Markov chains extending sofic systems are completed. To homomorphisms of sofic systems are canonically associated homomorphisms of Markov extensions. Also considered is a class of finitary codes for sofic systems.